Time history analysis of multi- storey building with basement story accounting for soil–structure interaction - Mushina, Jalal; Mushina, Wissam (Edelweiss Applied Science and Technology, 2024)
Soil-Structure Interaction (SSI) is the effects of the soil (underlying and surrounding the structure) on the response of the structure. This study is a contribution in the soil structure interaction (SSI) field, as this interaction affects the seismic behavior of structures. Two series of Time History data were used in the analysis of reinforced concrete moment resisting frame building consisting of 9 stories with embedded basement storey building. The two approaches of SSI modeling that are substructure approach and direct approaches were compared with each other. Generally, and within the limits of this study, it was found that the responses of Substructure approach were identical with that of the direct approach in the two cases for all stories except for the Ground storey. It seems that SSI affects the higher stories rather than the lower stoerys. The dynamic analysis results comparison between the two approaches of modeling soil structure interaction, favored the substructure approach on the direct approach as the direct approach is time consuming. Also, the study found out that modeling the structure with only vertical spring led to doubtable results, which reflect present that is choosing this method represents the worst option. On the other hand, and according to the analysis results, study suggested that keeping use the fixed approach in design buildings (with embedded portion) does not represent the better choice. It is concluded that, the responses of Substructure approach is identical with that of the Direct approach in all cases for all stories except for the Ground storey. It seems that SSI affects the higher stories rather than the lower storey.